Inhibitory of PANC-1 produced by Indonesian's Marine Sponge Endectyon delaubenfelsi Adapted to Nutrient Starvation. (December 2018) - Kurnianda, V; Mardiah, A; Karina, S; Agustina, S; Ulfah, M; Octavina, C; Syahliza, F; Ramadhan, M R; Purnawan, S; Kurnianda, V
Abstract: The bioactivity of Indonesian Marine Sponge Endectyon delaubenfelsi has been conducted on July 2018. The active metabolite based on bioassay guided-separation with several steps of chromatography. The FTIR spectrum shows that the active metabolite has N-H amine functional groups at 3434.6 cm −1 C-H methyl was detected at 3090.46 cm −1, and the fingerprint region at 1637.27 cm −1 as C-N imine. Based on the FTIR data shows indicate that the active compound as alkaloid. Metabolite active has activity IC50 = 0.2 ug / mL indicates that the active compound from of Endectyon delaubenfelsi has potential activity as the new model to the drug discovery against PANC-1 cell.